Giant cell tumour of the patella with local recurrence: successful management with excision, curettage and artificial bone grafting. (14th February 2018) - Morris, Timothy Mark; Gamie, Zakareya; Ghosh, Kanishka Milton; Rankin, Kenneth Samora
Abstract : Primary patellar neoplasms are rare, comprising 0.12% of primary bone tumours; thus, no standardised treatment related to staging exists. 70%–90% of primary patellar neoplasms are benign or intermediate with giant cell tumour (GCT) being the most common. GCTs are locally aggressive, have a high recurrence rate and metastasise in 1%–2%. We report the case of a 23-year-old man with histologically confirmed recurrent GCT of the patella to demonstrate that aggressive surgical management options described in the literature, such as patellectomy with or without complex reconstruction, may be excessive and cause patients undue morbidity. Initially, the patient underwent intralesional curettage with excellent recovery, but presented again with a local recurrence within a year. A further definitive operation was performed which included excision of the inferior pole followed by curettage of the patellar body and artificial bone grafting. The patient made a good recovery and at 5-year follow-up has maintained good function.